Social Media, Populism, and Identity in Shaping Political Polarization - Suffianor (Politeia : Journal of Public Administration and Political Science and International Relations, 2025)
Political polarization represents a critical challenge for modern democracies, influencing political discourse, weakening institutional stability, and eroding civic trust. This review synthesizes key drivers, consequences, and global variations to provide an integrated understanding of its impact on democratic governance. Literature was systematically retrieved from Scopus, Web of Science, and Google Scholar using keywords such as political polarization, affective polarization, partisan hostility, and democratic resilience. Studies were included if they addressed causes, consequences, or mitigation strategies within democratic contexts. The review synthesizes findings across quantitative, qualitative, and experimental research traditions. Findings show that polarization is fueled by the interaction of social media, populist rhetoric, and cultural identity conflicts, which collectively intensify both affective and ideological divisions. Consequences include reduced institutional effectiveness, weakened democratic norms, declining public trust, and heightened extremism. Comparative analysis reveals that advanced democracies tend to face ideologically rooted polarization, while developing democracies are more affected by identity-based and socio-economic divisions. Despite contextual differences, polarization consistently weakens democratic resilience and erodes social cohesion. The discussion connects these findings to theories of democracy, highlights systemic factors such as inequality and weak representation, and considers policy responses including institutional reform, civic education, and media regulation. Future research is recommended to adopt interdisciplinary, comparative, and longitudinal approaches. This review contributes a unique synthesis of interdisciplinary and cross-regional insights, underscoring the urgency of addressing polarization to safeguard democratic systems in an increasingly fragmented environment.